Genetic relatedness among chicken breeds using randomly amplified polymorphic DNA (RAPD) markers - SHARMA, A K; SINGH, R K; KUMAR, S; SHARMA, DEEPAK (The Indian Journal of Animal Sciences, 2014)
Randomly amplified polymorphic DNA (RAPD) markers were used to detect the DNA polymorphism in various chicken breeds. Ten decamer primers were screened and 5 of these generated the polymorphism within as well as between the chicken breeds. Using 5 selected primers, 36 (57.7%) out of 52 amplified bands, were polymorphic. Within breed genetic similarity ranged from 0.76 to 0.87 and in general exotic breeds showed higher genetic similarity as compared to the native breeds. Genetic similarity estimates between the populations ranged from 0.74. to 0.88. The native breeds showed maximum genetic similarity among themselves, while the White Leghorn showed lower genetic similarity with other breeds. Very close relationship among the native breeds was also evident from the dendogram, obtained from Nei coefficient of genetic similarity, while both the exotic breeds were clustered together.